The right to resettlement as a social right - Vela Hugo, Miguel (2021)
The need for social rights in developing countries is essential for the full development of the population both in different economic, cultural, technological, environmental, social aspects... etc. According to Article 1 of the Constitution of Peru person and his “dignity” are the supreme goal of society and the state, and in the case of social rights where the dignity of the disadvantaged or victims facts warrant random through public policies. One of the problems faced is that there is an ambiguity between the boundary of the private and the public, and this is be: cause many of the functions that promote social rights are services that can be found in the private sector, such as education and security. This causes a devaluation of these services from the state and in some cases a negligent attitude on the part of the administrative process. However, there are dis tinctions in the classification of negative and positive rights, one require the state to refrain from intervening or act in a certain way, another imposed to perform certain behaviors. The first group comprises the traditional civil and political rights, social rights second.